Mouth preparation pasien hemangioma bibir pada anak sebelum tindakan radioterapi - Irene Edith Rieuwpassa; Harun Achmad (DiscoverSys Inc., 2010)
Hemangioma is a vascular benign tumor frequently found in childhood and about30% manifests itself in head and neck areas. This lesion is frequently found in lip,tongue and buccal mucosal areas. Its etiology is conjectured to be related to theproliferation of abnormalities of endothelium cells. According to its type, hemangiomais divided into capillary, cavernous, and mixed hemangioma. Surgery is indicated incases that cause complications. A case of hemangioma was reported in the lower lipof an eight-year-old girl. The patient accompanied by her parents visited the SpecialDental Care Clinic, Department of Oral Surgery, Hasan Sadikin Hospital, Bandung,with the complaint of having reddish bruises on the lower lip, which impeded thespeaking and masticating function. Before radiotherapy was performed at theRadiology Polyclinic, mouth preparation was provided for all his teeth first, for thepurpose of improving oral hygiene and preventing focal infection present in theintraoral condition.